Need Analysis on Islamic Communication and Broadcasting Department of UIN Raden Mas Said Surakarta - Kaaba, Titin Suhartini; Nafila, Mauren Kyara (English Education Department, 2024)
This study aims to find out the students of Islamic communication and broadcasting department need in English subject. Currently, the students are taught the General English therefore, it makes the researcher conduct the research to reveal their need in ESP. The method used in this research is descriptive qualitative method. The participants are 40 students and 1 lecturer of Islamic Communication and Broadcasting Department of UIN Raden Mas Said Surakarta. The data was taken from questionnaire to students and interview to the lecturer which covers topic needed and teaching method. The results showed that the Islamic Communication and Broadcasting Department students’ need in ESP in varied range of topic.